2017
DOI: 10.3389/fpls.2017.00281
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of Wheat Cultivars to Combat Zinc Deficiency

Abstract: Zinc (Zn) deficiency caused by inadequate dietary intake is a global nutritional problem, particularly in developing countries. Therefore, zinc biofortification of wheat and other cereal crops is being urgently addressed and highly prioritized as a research topic. A field study was planned to evaluate the influence of zinc application on grain yield, grain zinc content, and grain phytic acid concentrations of wheat cultivars, and the relationships between these parameters. Three wheat cultivars, C1 = Faisalaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 48 publications
(86 reference statements)
5
87
0
1
Order By: Relevance
“…Foliar application of nutrients is an important crop management strategy to maximize crop yields and concentrations of micronutrients in edible parts. Several studies have demonstrated that foliar application of micronutrients, including Zn and Fe, showed good behavior in increasing their concentration in wheat grain [27,[48][49][50][51][52]. However, little is known about the effect of combined Zn and Fe on the quality of this wheat grain.…”
Section: Introductionmentioning
confidence: 99%
“…Foliar application of nutrients is an important crop management strategy to maximize crop yields and concentrations of micronutrients in edible parts. Several studies have demonstrated that foliar application of micronutrients, including Zn and Fe, showed good behavior in increasing their concentration in wheat grain [27,[48][49][50][51][52]. However, little is known about the effect of combined Zn and Fe on the quality of this wheat grain.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Zn-enriched grain did have a lower phytic acid content than in the grains with lower Zn content (Fig. 3C,D) [83].…”
Section: Varietal Screening Of Wheat For Zinc Efficiencymentioning
confidence: 87%
“…2). Maximum improvements in grain yield of 24.3% and 24.1%, and for Zn concentrations a maximum increase of 50.1% and 46.6% were recorded when Zn was applied in soil + foliar in both years, respectively, whereas the minimum improvement in grain yield was recorded for the zero-Zn plot [83]. Therefore, soil + foliar application of Zn appears to be an excellent strategy to increase grain Zn concentrations.…”
Section: Agronomic Biofortification Of Zincmentioning
confidence: 90%
See 2 more Smart Citations